ANALISIS ASUHAN KEPERAWATAN DENGAN TERAPI TEKNIK RELAKSASI BENSON UNTUK MENGURANGI NYERI DAN CEMAS PADA PASIEN HEMODIALISA - Tri Andhika Dessy Wahyuni (2022)
Anxiety and pain experienced by patients undergoing hemodialysis are often found in the Hemodialysis Unit, where this is caused by foreign equipment and machines as well as discomfort associated with stabbing the device. The purpose of writing this final scientific paper is to implement an evidence based nursing intervention, namely the Benson Relaxation Technique to reduce pain and anxiety in patients undergoing hemodialysis at the Hemodialysis Unit of Bhayangkari Hospital TK. 1 R. S. Sukanto Jakarta. Analysis of nursing care with the Benson Relaxation technique was carried out by patients undergoing hemodialysis therapy by measuring anxiety levels using the Beck Anxiety Inventory (BAI) questionnaire and measuring pain levels using the Numeric Rating Scale (NRS). The results of the implementation of the Benson Relaxation Technique are a significant reduction in the level of anxiety and pain in patients. However, with the authors' limitations, it is hoped that the implementation of the Benson Relaxation technique can be carried out on more patients in the Hemodialysis Unit in future studies to see the level of further effectiveness.